Reaching nearby sources: comparison between real and virtual sound and visual targets - Parseihian, Gaëtan; Jouffrais, Christophe; Katz, Brian F. G. (Frontiers in Neuroscience, 2014)
Sound localization studies over the past century have predominantly been concerned with directional accuracy for far-field sources. Few studies have examined the condition of near-field sources and distance perception. The current study concerns localization and pointing accuracy by examining source positions in the peripersonal space, specifically those associated with a typical tabletop surface. Accuracy is studied with respect to the reporting hand (dominant or secondary) for auditory sources. Results show no effect on the reporting hand with azimuthal errors increasing equally for the most extreme source positions. Distance errors show a consistent compression towards the center of the reporting area. A second evaluation is carried out comparing auditory and visual stimuli to examine any bias in reporting protocol or biomechanical difficulties. No common bias error was observed between auditory and visual stimuli indicating that reporting errors were not due to biomechanical limitations in the pointing task. A final evaluation compares real auditory sources and anechoic condition virtual sources created using binaural rendering. Results showed increased azimuthal errors, with virtual source positions being consistently overestimated to more lateral positions, while no significant distance perception was observed, indicating a deficiency in the binaural rendering condition relative to the real stimuli situation. Various potential reasons for this discrepancy are discussed with several proposals for improving distance perception in peripersonal virtual environments.